Pengaruh Kombinasi Probiotik dan Zinc terhadap Berat Badan Tikus Malnutrisi - Siti Thomas Zulaikhah; Perez Wahyu Purnasari (FORIKES, 2021)
Background: Single zinc supplementation has shown to be ineffective to reduce the national prevalence of malnutrition. Further research is needed in administration of combined probiotics and zinc supplementation on body weight in malnourished rats. Aim: This study is designed to assess effects of probiotics and zinc co-supplementation on body weight in malnourished rats. Methods: Experimental study with pre-and post-test control group design, 30 rats, aged 8 weeks, weighed 150-200g, were randomly divided into 5 groups. Group K(+), P1, P2, and P3 were given low calorie diet for 14 days to induce malnutrition. On the 15th day, all rats were weighed. The treatment was started on day 15 to 28, K(+) was still given low calorie diet, P1 was given probiotics and zinc combination, P2 was given probiotics, and P3 was given zinc. P1, P2, P3 were given standard diet. On the 29th day all the rats in each group were weighed. Results: Data were analyzed using paired sample t-test with obtained p-value of 0.000 (p 0,05). Hasil: Uji Paired sample t-test diperoleh p-value = 0,000 (p